Prospective Study of a Cohort of Russian Nijmegen Breakage Syndrome Patients Demonstrating Predictive Value of Low Kappa-Deleting Recombination Excision Circle (KREC) Numbers and Beneficial Effect of Hematopoietic Stem Cell Transplantation (HSCT) - Deripapa, Elena; Balashov, Dmitry; Rodina, Yulia; Laberko, Alexandra; Myakova, Natalya; Davydova, Nataliia V.; Gordukova, Maria A.; Abramov, Dmitrii S.; Pay, Galina V.; Shelikhova, Larisa; Prodeus, Andrey P.; Maschan, Mikhail A.; et al. (Frontiers in Immunology, 2017)
Background: Nijmegen Breakage Syndrome (NBS) is a combined primary immunodeficiency with DNA repair defect, microcephaly, and other phenotypical features. It predominantly occurs in Slavic populations that have a high frequency of carriers with the causative NBN gene c.657_661del5 mutation. Due to the rarity of the disease in the rest of the world, studies of NBS patients are few. Here we report a prospective study of a cohort of Russian NBS patients. Methods: 35 Russian NBS patients of ages 1-19 years, referred to our Center between years 2012 and 2016, were prospectively studied. Results: Despite the fact that in 80% of the patients microcephaly was diagnosed at birth or shortly thereafter, the average delay of NBS diagnosis was 6.5 years. Though 80% of the patients had laboratory signs of immunodeficiency, only 51% of the patients experienced significant infections. Autoimmune complications including interstitial lymphocytic lung disease and skin granulomas were noted in 34%, malignancies – in 57% of the patients. TREC\KREC levels were low in the majority of patients studied. Lower KREC levels correlated with autoimmune and oncological complications. Fifteen patients underwent hematopoietic stem cell transplantation (HSCT), ten of them were alive and well, with good graft function. Three patients in the HSCT group and five non-transplanted patients died; tumor progression being the main cause of death. The probability of the overall survival since NBS diagnosis was 0.76 in the HSCT group and 0.3 in the non-transplanted group. Conclusions: Based on our findings of low TRECs in most NBS patients, independent of their age, TREC detection can be potentially useful for detection of NBS patients during the neonatal screening. KREC concentration can be used as a prognostic marker of disease severity. HSCT is a viable treatment option in NBS, and should be especially considered in patients with low KREC numbers early on, before development of life threatening complications.